Building the genomic nation: 'Homo Brasilis' and the 'Genoma Mexicano' in comparative cultural perspective. (December 2015) - Kent, Michael; García-Deister, Vivette; López-Beltrán, Carlos; Santos, Ricardo Ventura; Schwartz-Marín, Ernesto; Wade, Peter
This article explores the relationship between genetic research, nationalism and the construction of collective social identities in Latin America. It makes a comparative analysis of two research projects – the 'Genoma Mexicano' and the 'Homo Brasilis' – both of which sought to establish national and genetic profiles. Both have reproduced and strengthened the idea of their respective nations of focus, incorporating biological elements into debates on social identities. Also, both have placed the unifying figure of the mestizo/ mestiço at the heart of national identity constructions, and in so doing have displaced alternative identity categories, such as those based on race. However, having been developed in different national contexts, these projects have had distinct scientific and social trajectories: in Mexico, the genomic mestizo is mobilized mainly in relation to health, while in Brazil the key arena is that of race. We show the importance of the nation as a frame for mobilizing genetic data in public policy debates, and demonstrate how race comes in and out of focus in different Latin American national contexts of genomic research, while never completely disappearing.